The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1089/ther.2016.0016
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Induction of Therapeutic Hypothermia Using Transnasal High Flow Dry Air

Abstract: Early induction of therapeutic hypothermia (TH) is recommended in out-of-hospital cardiac arrest (CA); however, currently no reliable methods exist to initiate cooling. We investigated the effect of high flow transnasal dry air on brain and body temperatures in adult porcine animals. Adult porcine animals (n = 23) under general anesthesia were subject to high flow of transnasal dry air. Mouth was kept open to create a unidirectional airflow, in through the nostrils and out through the mouth. Brain, internal ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Intrinsic mechanisms of local blood flow redistribution and air flow rate variations into nasal mucosa can not only modulate brain temperature, but also contribute to blood and core temperature regulation. High-flow oxygen through the upper airways of intubated rats resulted in a flow-dependent decrease in brain temperature (Einer-Jensen and Khorooshi, 2000), which was later confirmed in porcine models using transnasal dry air (Chava et al, 2017). This study showed that the rate of brain cooling was significantly higher at higher airflow rates, independent of the air temperature, and was eliminated by humidifying the air, consistent with principles of evaporative cooling.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Intrinsic mechanisms of local blood flow redistribution and air flow rate variations into nasal mucosa can not only modulate brain temperature, but also contribute to blood and core temperature regulation. High-flow oxygen through the upper airways of intubated rats resulted in a flow-dependent decrease in brain temperature (Einer-Jensen and Khorooshi, 2000), which was later confirmed in porcine models using transnasal dry air (Chava et al, 2017). This study showed that the rate of brain cooling was significantly higher at higher airflow rates, independent of the air temperature, and was eliminated by humidifying the air, consistent with principles of evaporative cooling.…”
Section: Discussionsupporting
confidence: 70%
“…The primary purpose of the turbinates is to warm and humidify inspired air before it reaches the sensitive tissue of the lungs. The heat transfer involved in liquid to gas phase change of nasal mucous results in heat loss, which in turn is proportional to the air flow rate setting and therapy duration (Chava et al, 2017).…”
Section: Coolstat Devicementioning
confidence: 99%
See 1 more Smart Citation
“…The cooling effect appears to be highly dependent on the airflow rate and air dryness, as lower flow rates and humidification of the inflowing air mitigate the cooling effect. [73] The PRINCE trial, a randomized multicenter study, investigated the effects of TEC using a mixture of PFC and high-flow oxygen in patients with witnessed CA and [55] 1998…”
Section: Intranasal Coolingmentioning
confidence: 99%
“…Safety of this approach, given the high flow exposure to the nasal mucosa of dry gas in these patients, was further assessed by an ear, nose and throat consultant as part of the team. This approach has been previously reported to be effective in pigs [3], and other related approaches such as the use of perfluorocarbon nasal sprays and/or nasal cooling balloons have also demonstrated success in patients and pigs, respectively [4,5].…”
mentioning
confidence: 99%